Desain Merchandise Gerakan Earth Hour Di Kota Batu Sebagai Media Informasi - Anifatul Izzah; Elfa Olivia Verdiana (Lembaga Penelitian Pengembangan dan Pengabdian Kepada Masyarakat STMIK Asia Malang, 2023)
There are many communities in Indonesia today, ranging from education, health, welfare, animal protection to the environment. Earth Hour is a community that cares about the environment that moves to invite the public to take small actions with big changes initiated by WWF. In 2019, the Earth Hour community was officially spread in 33 cities in Indonesia, including in Batu City, it's just that information about the movements or actions carried out by the Batu City Earth Hour Community is not understood by the public. The solution offered in this research is the design of the merchandise design for the Earth Hour movement in Batu City as a medium of information. Where merchandise is an easy way to get to know the community and raise a good image. The results of the test using the questionnaire method in this study, showed that the percentage of